2021
DOI: 10.1186/s13256-021-02830-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell neuroendocrine tumor of the prostate: a case report and review of the literature

Abstract: Background Primitive neuroendocrine prostate neoplasms are rarely reported. This entity comprises carcinoïd tumors and poorly differentiated neuroendocrine tumors, mainly those of the small-cell type. Large-cell-type primitive tumors are exceptional, and only nine cases are reported in the literature. Similar to neuroendocrine tumors of the prostate, large-cell-type primitive tumors may be observed in the context of conventional adenocarcinoma during androgen deprivation therapy or as prostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Sleiman et al [15] made the following conclusions: • Large-cell primary neuroendocrine carcinoma of the prostate gland is an aggressive as well as a rare histological entity.…”
Section: ] •mentioning
confidence: 99%
See 4 more Smart Citations
“…Sleiman et al [15] made the following conclusions: • Large-cell primary neuroendocrine carcinoma of the prostate gland is an aggressive as well as a rare histological entity.…”
Section: ] •mentioning
confidence: 99%
“…Sleiman et al [15] reported a 68-year-old Caucasian patient who had manifested in September 2015 with an elevated serum prostate-specific antigen (PSA) level. The patient's past medical history included diabetes mellitus, hypertension, dyslipidemia, hyperuricemia as well as mild renal failure.…”
mentioning
confidence: 99%
See 3 more Smart Citations